Beyond Autonomy: An Actor-Network Theory Study of a Solo Exhibition in Indonesia - Bastari, Rendy Pandita; Aditia, Patra; Nabila, Ganesha Puspa (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2026)
In many exhibition artists are often perceived as singular and autonomous actors. Departing from the critique of this tendency, this study examines the solo exhibition Toyscapes, After Us by Indonesian artist Hilman Hendarsyah (November 2025) as a case study through the lens of Actor-Network Theory (ANT), in order to understand art exhibition as relational and socio-material practices. This study traces how exhibitions are produced through interaction between human and non-human actors within heterogeneous network. The analysis was conducted by following the actors and mapping processes of problematization, translation, and network stabilization. The findings elucidates that solo exhibition cannot be understood as autonomous artistic expression, but rather as an effect of network assembly involving the artist, curator, gallery management, exhibition space, production deadlines, transportation systems, and other material devices. The findings in this study shows six categorical actors, namely human actors, institutional actors, material actors, spatial actors, temporal actors, and cultural-symbolic actors. Non-human elements in these categories are shown to function actively as mediators that both constrain and enable artistic and curatorial decision-making. This study contributes to the development of art studies and exhibition management scholarship in Indonesia by offering an empirical application of ANT within the context of small-scale galleries.